[Grinding stone] - (:unkn) unknown (The Public Relations Department. Caroni (1975) Limited, Trinidad and Tobago, 2013)
Each estate had a grinding stone for the sharpening of cutlasses. At the end of each day workers would sharpen their cutlass for the next day of work.
Cataloger's title
Keywords: Sharpening of tools; Machetes -- Trinidad and Tobago